Aazhi Aran: Lorawan-Enabled Intelligent Maritime Border Security and Crew Safety System (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Fishing communities operating in remote maritime environments face significant safety challenges due to unreliable communication systems, unclear international sea borders, harsh weather conditions, and delayed emergency response. These factors often lead to accidental border crossings and hazardous situations, threatening the lives of fishermen. To address these issues, this paper proposes a LoRaWAN-Enabled Intelligent Maritime Border Security and Crew Safety System that provides a reliable and energy- efficient solution for enhancing maritime safety.The proposed system is built using an ESP32 LoRa module integrated with a GPS module, DHT11 temperature and humidity sensor, air quality sensor, DC motor with motor driver, buzzer, LCD display, and an emergency switch. The GPS module continuously monitors the real-time location of the fishing boat, while predefined maritime boundary coordinates are used to detect proximity to restricted zones. Environmental conditions inside the boat are monitored using the DHT11 and air quality sensors to ensure crew safety.The system operates on a three-level safety mechanism. Level 1 provides early warnings through visual and audible alerts, Level 2 issues danger alerts with motor speed reduction, and Level 3 initiates critical actions such as automatic motor reversal to prevent border crossing. Environmental threshold violations also trigger alerts to notify the crew.In emergency situations, fishermen can activate the emergency switch to transmit distress signals along with GPS coordinates via LoRaWAN. The system also supports boat-to-boat communication, enabling nearby vessels to share alerts and assist each other without relying on cellular networks.The proposed system is cost-effective, reliable, and suitable for small-scale fishing operations. It enhances safety by integrating border monitoring, environmental sensing, and long-range communication in a single platform.